Spoil Pile Instability with Reference to the Goonyella Mine, Queensland (The Australasian Institute of Mining and Metallurgy, 1981)
The characteristics and causes of the spoil pile failures at the Goonyella Mine are described, and research results from investigations of spoil pile instability are discussed. Some effects on spoil stability of the development of deep strip mining projects are considered and recommendations are made for relevant research.